ETNOPHARMACOLOGY OF SPICES AS TRADITIONAL MEDICINE IN ACEH RURAL COMMUNITIES CENTRAL ACEH - Ernilasari, Ernilasari; Yuslinaini, Yuslinaini; Saudah, Saudah; Ahadi, Rizky (Universitas Islam Negeri Ar-Raniry, 2022)
The use of spice plants as medicine and potions cannot be separated from the culture and local wisdom adopted, so that in practice, special knowledge and skills are needed to produce drugs and potions that are believed to be able to maintain health and cure various diseases. The purpose of this study was to obtain information from the Rural Communities of Central Aceh about utilization of spices in traditional medicine. This research was conducted on the Paya Tungel Villagers, Jagong Jeget District, Central Aceh. This study used an exploratory survey method with purposive sampling. Data collection was carried out by semi-structured interviews with predetermined correspondents, and direct observations of spice plants in the field. Based on the results of the study, there are 21 species of spices used as medicine belonging to 9 families. Spices are used for health maintenance, anti-pain, anti-inflammatory and healing of infectious diseases and other metabolic disorders. The most widely used part of the plant is the rhizome. The most processing is boiling and then consuming it by drinking.